Can a Non-Nationalist Art History be Written?d: Několik poznámek ke kontraproduktivní polarizaci poznávacích zájmů v humanitních vědách - Bartlová, Milena (Dějiny – teorie – kritika, 2024)
The classical, formalist methods of art history seem to be inevitably intertwined with both the "great story" and with ethnic (racial) identifications of the artistic heritage. Even if the categories of "style" and "evolution" can be evaded, this would leave a ground plan in which national state was the basic matrix for writing the kind of coherent art historical narrative still in demand from both the general public and educational systems. Histories of the art of the Central European states, e.g. of Hungary and Slovakia, are burdened by the need to define their object, and not to fall into the trap of nationalism. This is methodologically much more difficult than is generally realised. Possible operations include, in the first instance, suspension of the idea of any essential ethnic regional identity. A necessary caution must be exercised in using the classical art historical methods employed for research into art from "anonymous epochs", since national, ethnic or racial identifications are ingrained deep in their texture.